Overview of sugarcane harvester virtual design in China - Wang Jun; Hu Jinbing; Wu Jianfeng (浙江大学学报. 农业与生命科学版)
Many developed countries, such as Austria and America, have been accomplished the mechanization fully during the sugarcane production. The development of some mechanical manufacturing is on the way to automated and intelligent direction. From the 1960s to nowadays, our research on the sugarcane harvest mechanization has a history of over 40 years. However, except for the mechanization realization of the plowing land preparation and transportation, the biggest harvest of labor still relies on the human, which makes the production efficiency be extremely low. With the increasing area of the sugarcane planting, the mode of production of the traditional manual harvest can not meet the need of the modern agriculture development anymore.Nowadays, the harvest is in the low level and the production efficiency is also not so much high as the sugarcane mechanization, moreover, there has been no such a machine that can adapt to the reality of our country with substantial promotion. This paper outlines the characteristics of sugarcane harvest machinery on the basis of the method of the agricultural equipment virtual design. At the same time, this paper analyses the existing problem and the research direction, which lays a foundation for sugarcane harvest design and the future development.First, this paper will introduce the concept of the virtual design as well as the three characteristics of immersion, simplicity and instantaneity. Based on the practical situation of the research on the sugarcane harvester virtual design, this paper highlights the application research status of virtual design in whole virtual design, hand cane mechanism, cutting mechanism, peeling leaves, logistics simulation and so on. Combined with the development and the promotion of the sugarcane harvest mechanization, it analyses the problem and the limitation of the sugarcane institutions, stripping leaves institutions, logistics simulation and virtual design, and the research directions in the future are also be put forward.On the research applications of the sugarcane harvester, virtual design has some problems and limitations which are as follows: Sugarcane is not in conformity with the actual mode; the combination of the virtual design and the agronomic requirements is very little; the combination of the virtual design and the machine battery solution is little too; the model of the virtual machine is not perfect enough. In order to solve these problems and limitations, this paper puts forward that we should carry out the research from the perspective of the key institutions and in combination with the advantages of virtual design. It mainly conducts further research from the following aspects: Physical characteristics of sugarcane research, combined with the agronomic requirements and the machine battery solution, and the virtual prototype model will be perfected.As the method of the new product development design and the optimization of improvement, the virtual design not only simplifies the design of the complex mechanical system, but also shortens the development cycle of new products, improves the design quality, and reduces the development cost largely. Nowadays, the virtual design still has some problems on the application research of the sugarcane harvester, especially for the aspects of these questions and limitations, the further research will be conducted. Completing the virtual prototype model, at the same time, providing the theoretical foundation for producing the physical prototype, and then our sugarcane harvester will be perfectly developed and promoted.